Bilateral anterior opercular syndrome - Naqash, Mohd Mubarik; Ahmad, Feroze; Bhat, Arif Nabi; Jalalie, Umar (International Journal of Research in Medical Sciences, 2017)
Opercular syndrome, also known as Foix-Chavany-Marie syndrome is a rare disorder due to bilateral lesions of opercular cortex surrounding the insula. It is characterized by paralysis of facial, lingual, pharyngeal, and masticatory voluntary muscles with preservation of autonomic, involuntary, and reflexive functions. In the present case, a 71-years old female presented with acute onset of anarthria with difficulties in chewing, speaking, and swallowing that was diagnosed with opercular syndrome.